2013
DOI: 10.2478/s11686-013-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Dirofilaria immitis in mid-western arid Argentina

Abstract: Dirofilariosis, caused by Dirofilaria immitis and D. repens, is (re-) emerging worldwide. Dogs are the main reservoirs, while human infection has recently become an important focus of interest and attention. In Argentina, canine D. immitis infection has been described in eastern and northern subtropical and temperate humid regions, but never reported in mid-western arid regions so far. In this research note we report for the first time the occurrence of autochthonous human and canine D. immitis infection in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Dirofilariosis caused by D. immitis has been reported in Buenos Aires [254256] and Mendoza [257]. Epidemiological studies in Argentina suggest that the prevalence of dirofilariosis in dogs is highly variable, showing a significantly heterogeneous temporal and spatial distribution [254256, 258, 259].…”
Section: Country Filesmentioning
confidence: 99%
“…Dirofilariosis caused by D. immitis has been reported in Buenos Aires [254256] and Mendoza [257]. Epidemiological studies in Argentina suggest that the prevalence of dirofilariosis in dogs is highly variable, showing a significantly heterogeneous temporal and spatial distribution [254256, 258, 259].…”
Section: Country Filesmentioning
confidence: 99%
“…Only few reports are available for CVBD in Argentina and, as in many countries in Latin American, most are related to parasitic diseases such as babesiosis [1, 2], hepatozoonosis [2, 3], dirofilariasis [47], leishmaniasis [8–15] and trypanosomiasis [8, 1623]. …”
Section: Introductionmentioning
confidence: 99%
“…It is arguably the most important parasite of dogs in North America. As of 2013, heartworm-positive dogs had been reported in every state in the continental USA (Wang et al 2014;Yancey et al 2014), and in multiple countries in South America (confirmed reports in Argentina, Colombia, Peru and Brazil, though recent data are sparse from the other countries) (Labarthe and Guerrero, 2005;Vezzani et al 2011a, b;Cuervo et al 2013;Labarthe et al 2014), as well as Southern Europe, Australia and parts of Africa (Simon et al 2009;Barker et al 2012;Otranto et al 2013;Maia et al 2015). In Europe, the parasite seems to be spreading into previously non-endemic areas, especially in Central Europe (Penezic et al 2014;Sassnau et al 2014;Tolnai et al 2014).…”
Section: Introductionmentioning
confidence: 94%
“…2014; Yancey et al 2014), and in multiple countries in South America (confirmed reports in Argentina, Colombia, Peru and Brazil, though recent data are sparse from the other countries) (Labarthe and Guerrero, 2005; Vezzani et al . 2011 a , b ; Cuervo et al 2013; Labarthe et al 2014), as well as Southern Europe, Australia and parts of Africa (Simon et al 2009; Barker et al . 2012; Otranto et al .…”
Section: Introductionmentioning
confidence: 99%